2014
DOI: 10.1097/md.0000000000000055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Breastfeeding on Childhood BMI and Obesity

Abstract: The objective of this study is to investigate the effect of breastfeeding on childhood obesity in China.We used data collected from the China Family Panel Studies, an ongoing, prospective, and nationwide longitudinal study to explore the extensive and dynamic social changes in China. A total of 7967 children were included in the analysis. Duration of breastfeeding was first treated as a continuous variable and subsequently dichotomized into ever versus never, ≥6 months versus <6 months, ≥8 months versus < 8 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…This source of confounding is a potent source of bias in all observational studies of infant feeding and adiposity, including in our study. Although systematic reviews point to a negative association with overweight and obesity (8)(9)(10)(11)(12), some findings are still controversial (13,14,40,41). Our data from 4 multinational cohorts followed prospectively from birth to 6 and 20 y in one cohort provide an important and unprecedented contribution to the literature.…”
Section: Strengths and Limitationsmentioning
confidence: 68%
See 1 more Smart Citation
“…This source of confounding is a potent source of bias in all observational studies of infant feeding and adiposity, including in our study. Although systematic reviews point to a negative association with overweight and obesity (8)(9)(10)(11)(12), some findings are still controversial (13,14,40,41). Our data from 4 multinational cohorts followed prospectively from birth to 6 and 20 y in one cohort provide an important and unprecedented contribution to the literature.…”
Section: Strengths and Limitationsmentioning
confidence: 68%
“…Furthermore, the large RCT from Belarus (14) found no association between breastfeeding and instrumental variable analyses in intention-totreat, observational, and instrumental variable analyses. More recently a Chinese study found no association between breastfeeding and BMI, although the data on breastfeeding duration in the Chinese study were collected retrospectively (40). Further, a Dutch study showed that overweight infants would become overweight children regardless of feeding method (41).…”
Section: Discussionmentioning
confidence: 99%
“…While this study substantiates current literature describing the protective effects of breastfeeding, some published research purports that breastfed infants are just as likely to be overweight or obese as non-breastfed children. 2021 Uwawzuoke, Eneh, and Ndu 10 suggested that a positive relationship between breastfeeding and healthy childhood weight outcomes only highlighted the exclusion of possible confounders, in their 2017 review article. These authors concluded that breastfeeding was not related to pediatric obesity, but rather the observed protective effects may be a result of sociodemographic confounders, such as maternal obesity and maternal smoking.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms regarding the effect of breastfeeding on the risk of overweight remain inconclusive. In contrast, several studies failed to establish a significant association between breastfeeding and childhood overweight [ 67 , 68 , 69 , 70 , 71 ]. A potential explanation for the discrepancy in the findings might be the difference in sample size, population age, proportion of breastfeeding, study design or diverse population (genetic and environmental background).…”
Section: Discussionmentioning
confidence: 99%